2012
DOI: 10.1186/1742-4755-9-30
|View full text |Cite
|
Sign up to set email alerts
|

Do Malawian women critically assess the quality of care? A qualitative study on women’s perceptions of perinatal care at a district hospital in Malawi

Abstract: BackgroundMalawi has a high perinatal mortality rate of 40 deaths per 1,000 births. To promote neonatal health, the Government of Malawi has identified essential health care packages for improving maternal and neonatal health in health care facilities. However, regardless of the availability of health services, women’s perceptions of the care is important as it influences whether the women will or will not use the services. In Malawi 95% of pregnant women receive antenatal care from skilled attendants, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
143
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(154 citation statements)
references
References 42 publications
8
143
2
1
Order By: Relevance
“…This was supported with the study conducted in Malawi which stated that health workers' attitudes are a great challenge in the provision of health care particularly during labor and delivery as deterred pregnant and laboring women from utilizing health services [10].…”
Section: Discussionsupporting
confidence: 58%
“…This was supported with the study conducted in Malawi which stated that health workers' attitudes are a great challenge in the provision of health care particularly during labor and delivery as deterred pregnant and laboring women from utilizing health services [10].…”
Section: Discussionsupporting
confidence: 58%
“…28 Some qualitative studies done in Malawi reveal negative attitudes among some nurses. 8,20,21 The differences in findings between these studies and the present study may be attributable to differences in the methodological approaches used in data collection. The positive attitudes of the nurses towards nursing care may have several possible explanations.…”
Section: Nurses' Attitudescontrasting
confidence: 65%
“…19 Studies conducted in Malawi have reported that negative attitudes among nurses are sometimes manifested by rudeness and scolding of patients. 8,20,21 Such behaviours are associated with job dissatisfaction among nurses. [22][23][24] Patient and public complaints about the quality of nursing care in Malawi may be related to negative attitudes among nurses who are dissatisfied with their jobs.…”
Section: Introductionmentioning
confidence: 99%
“…Management of complications as necessary, in addition to good health of the mother and child, are the most desirable aspect of care expressed by the women in this study as well as others,, as these elements affect their health and survival [27,37,41]. Similarly, inadequate information sharing with women and her family, disrespectful treatment by staff and poor provider attitude, are perceived to equate with poor quality by women in our study and others, and can be a deterrent for further seeking care in health facilities [4346,60–66]. …”
Section: Discussionmentioning
confidence: 74%